Obsessive Symptoms Associated with Lamotrigine use in a Patient with Bipolar II Disorder - Kuloglu, Murat; Ekinci, Okan; Yilmaz, Elif; Caykoylu, Ali (Kure Iletisim Grubu A S, 2009)
Lamotrigine has been found to be efficacious in the acute management of bipolar depression and long-term management of bipolar disorder. Currently, it is increasingly used in the treatment of bipolar depression. Literature associated with obsessive symptoms related to lamotrigine treatment is limited. We report a case of bipolar II disorder that was successfully treated with pharmacological augmentation of lamotrigine plus venlafaxine and also subsequently experienced obsessive symptoms during treatment with lamotrigine.
Keywords: Lamotrigine; obsession; glutamate; bipolar disorder